2016
DOI: 10.1097/brs.0000000000001229
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of the SRS-Schwab Classification for Degenerative Lumbar Scoliosis

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 21 publications
5
28
1
Order By: Relevance
“…As described by Aebi [7], the clinical characteristics and pathophysiology of DNDLS are different compared with other forms of ASD. This has been supported by studies which found very weak correlation between health outcomes and sagittal plane deformity, when limiting ASD to DNDLS [50,51]. It is, therefore, most likely that a distinction between the subtypes of ASD, such as DNDLS, should be made in determining the clinical course.…”
Section: Insufficient Evidencementioning
confidence: 86%
“…As described by Aebi [7], the clinical characteristics and pathophysiology of DNDLS are different compared with other forms of ASD. This has been supported by studies which found very weak correlation between health outcomes and sagittal plane deformity, when limiting ASD to DNDLS [50,51]. It is, therefore, most likely that a distinction between the subtypes of ASD, such as DNDLS, should be made in determining the clinical course.…”
Section: Insufficient Evidencementioning
confidence: 86%
“…Although previous studies have demonstrated the importance to improve the PI‐LL, the optimal PI‐LL for corrective surgery remains controversial. This was the first study to exclusively investigate the association between postoperative PI‐LL and postoperative clinical outcomes based on three SRS‐Schwab PI‐LL sagittal modifiers (<10°, “0”; 10°–20°, “+”; >20°, ++) in ADS who underwent long posterior instrumentation and fusion.…”
Section: Discussionmentioning
confidence: 99%
“…The spinal regions are not independent of one another, and CL as an adaptive spinal segment depends on the alignment of both thoracic and lumbar spine. In previous studies of sagittal spinal parameters, Schwab et al proposed a simple approach of "lumbar lordosis = pelvic incidence ± 9°", which has been verified good correlation with HROQL and applied in most reconstructive surgeries at the thoracic and lumbar spine [5,17,18]. Therefore, for the cervical spine, further prospective study of the relationship between predictive CL and postoperative HRQOL outcomes is needed to find out whether predictive CL predicted only by cervical sagittal parameters actually can be applied to surgical planning.…”
Section: Discussionmentioning
confidence: 99%